A novel route to prepare a Ti3SnC2/Al2O3 composite. (1st April 2017) - Wang, Shuai; Cheng, Jun; Zhu, Shengyu; Ma, Jiqiang; Qiao, Zhuhui; Yang, Jun; Liu, Weimin
Abstract: In this study, a Ti3 SnC2 /Al2 O3 composite was successfully synthesized from Ti3 AlC2 and SnO2 . Al atoms in Ti3 AlC2 could react with SnO2 to generate Sn and Al2 O3, leaving behind the intact Ti3 C2 layers. The generated Sn atoms could diffuse into the Ti3 C2 layers to form Ti3 SnC2 or Ti3 Alx Sn1 − x C2 solid solutions. Considering the good diffusivity and high chemical reactivity of Al atoms, the use of appropriate oxides in the sintering of Al-containing M n + 1 AX n ceramics may provide a new approach to synthesizing, or discovering, other new M n + 1 AX n phases or solid solutions. Graphical abstract: